PANDANGAN AL-QURAN DALAM MENYIKAPI MARRIAGE IS SCARY: Analisis Tafsir Audiovisual Ustaz Rifky Ja'far pada Kanal YouTube Sayap Dakwah TV - Savira Manzilina; Ahmad Zaidanil Kamil (Program Studi Ilmu Al-Qur'an dan Tafsir, 2024)
This paper discusses the Qur'anic view on the issue of marriage is scary with the perspective of Ustaz Rifky Ja'far on the Dakwah Sunnah TV YouTube channel. This study, which is processed as a podcast, raises an issue that is being discussed by a number of young people in generation Z, which has the effect of making young people afraid to step into marriage. The purpose of writing this article is to analyse the view of the Qur'an in addressing the issue and examine how the da'wah approach delivered is able to offer relevant solutions to the fears and concerns of today's young generation in marriage. The method used uses digital ethnography and the theory of countering radicalism narratives initiated by Jeffery R. Halverson. Ustaz Rifky Ja'far explained his argument in refuting the issue with two verses in the Qur'an, namely in surah an-Nur [24]:32 about its virtue, namely that it can bring sustenance to someone who performs marriage, even though they are still not classified as capable, and surah ar-R??m [30]:21 about its virtue, namely giving peace to those who perform marriage. In this study, three forms of counter-narrative were found in the video delivered by Ustaz Rifky Ja'far, namely figural narrative; analogy narrative; and ideological narrative with two counter-narrative strategies of Ustaz Rifky Ja'far's extremism on the issue of marriage is scary, namely prioritising the qisas verse over the marriage verse and applying it to the realities of marriage.